Does maximal strength or speed-strength have stronger associations with performance indicators in the rugby football codes? A systematic review and meta-analysis - James, L. P.; Kelly, V. G.; Weakley, J.; Johnston, R. D.; Huynh, M. (Sports Medicine, 2026)
Background: Both maximal strength and speed-strength are considered key aspects of rugby league and rugby union match-play yet represent distinct physical qualities. Establishing whether maximal strength or speed-strength has a greater association with game performance in these sports can help direct resistance training interventions towards the physical quality most likely to transfer to the outcome of interest. It is therefore important to develop a clearer understanding of whether it is maximal strength or speed-strength that has stronger links to key aspects of rugby union and rugby league competition. Objectives: To systematically review and meta-analyse the literature to compare maximal strength versus speed-strength measures in their associations with within-game key performance indicators (KPIs) in rugby union and rugby league. Further, sub-group analysis was undertaken to determine whether the type of KPI (tackles, rucks, line breaks, carries/hit-ups, errors, and miscellaneous) moderated the extent to which the observed effect favoured maximal strength or speed-strength for a given KPI. Methods: A systematic search, conducted in accordance with PRISMA guidelines, of Web of Science, PubMed, and SportDiscus was conducted up to December 2024. Studies meeting the inclusion criteria provided correlation coefficients that were converted into Fisher`s z-transformed effect sizes to standardise the measures and allow for consistent comparison across studies. These effect sizes were analysed using a multivariate meta-analysis framework. Results: Six studies containing 41 maximal strength versus speed-strength comparisons and 134 players were included in the final analysis. Of the 786 studies initially identified, 28 underwent full-text screening, with 22 ultimately excluded. The overall pooled effect was 0.24 [0.11: 0.37] in favour of strength; however, the prediction interval ranged from g = - 0.58 to g = 1.06. The moderator analysis revealed a statistically significant effect of type (p = 0.038), indicating stronger associations for maximal strength compared to speed-strength. Residual heterogeneity (p = 0.005) suggested substantial variability in effect sizes across studies that was not fully explained by the model. Conclusions: Within-game rugby union and rugby league KPIs typically have stronger links to maximal strength than to speed-strength. However, the wide prediction interval underscores that the observed maximal strength advantage may not generalise across all types of KPIs or predictably translate to all future settings.